Odpowiedzi

2010-02-25T18:25:46+01:00
A) -3 ( x - 2y + 1 ) + 4 ( 2x + y - 12) = - 3x + 6y - 3 + 8x + 4y - 48 = 5x + 10y - 51
5 ( x + 3y - 2 ) - 2 ( x - 5y + 3 ) = 5x + 15y - 10 - 2x + 10y - 6 = 3x + 25y - 16
Najlepsza Odpowiedź!
2010-02-25T18:26:15+01:00
A) -3 ( x - 2y + 1 ) + 4 ( 2x + y - 12) = -3x + 6y - 3 + 8x + 4y - 48 = 10y + 5x -51

b)5 ( x + 3y - 2 ) - 2 ( x - 5y + 3 ) = 5x + 15y - 10 - 2x + 10y - 6 = 3x + 25y - 16
2010-02-25T18:26:43+01:00

a)-3x-6y-3+8x+4y-48=5x-2y-51
b)5x+15y-10-2x+10y-6=3x+25y-16